Perilaku Hand Hygiene dalam Pencegahan Covid-19 pada Perawat - La Asu, Supardin; Brajakson Siokal; Sudarman; Ernasari (Window of Nursing Journal, 2024)
Health workers are on the front line, especially as nurses who are always next to patients 1 x 24 hours. We must take precautions by means of hand hygiene before and after carrying out nursing care, where the COVID-19 outbreak is spreading very quickly resulting in an increase in the number of patients in the whole world. To reduce and prevent the transmission of this virus, we as nurses in providing nursing care must carry out hand hygiene and comply with WHO's 5 moments of hand hygiene, namely before touching a patient, before a clean or aseptic procedure, after exposure to or risk of body fluids. This study aims to determine the analysis of hand hygiene behavior in preventing COVID-19 among nurses at the Labuang Baji Regional General Hospital, Makassar City. The research design used is a quantitative research design with a crosssectional approach. The sample determination was carried out using a random sampling research method with a sample size of 83 respondents. The relationship test was carried out using the chi-square statistical test with a significance level (ρ) ≤ 0.05. The research results showed that the level of knowledge of nurses in the good category was 27 people (32.5%); the attitude of nurses in the positive category was 59 people (71.1%); there is no relationship between knowledge and hand hygiene behavior (p=0.786); and there is no relationship between attitude and hand hygiene behavior (p=0.372). The conclusion of this research is that there is no influence of nurses' knowledge and attitudes about hand hygiene on COVID-19 prevention measures at the Labuang Baji Regional General Hospital, Makassar City. It is recommended for future researchers to improve the implementation of hand hygiene among nurses in the motivation and work of PPI.